Virological outcomes of boosted protease inhibitor-based first-line ART in subjects harbouring thymidine analogue-associated mutations as the sole form of transmitted drug resistance. (13th December 2018) - Geretti, Anna Maria; White, Ellen; Orkin, Chloe; Tostevin, Anna; Tilston, Peter; Chadwick, David; Leen, Clifford; Sabin, Caroline; Dunn, David T; ,
Abstract: Objectives: In subjects with transmitted thymidine analogue mutations (TAMs), boosted PIs (PI/b) are often chosen to overcome possible resistance to the NRTI backbone. However, data to guide treatment selection are limited. Our aim was to obtain firmer guidance for clinical practice using real-world cohort data. Methods: We analysed 1710 subjects who started a PI/b in combination with tenofovir or abacavir plus emtricitabine or lamivudine, and compared their virological outcomes with those of 4889 patients who started an NNRTI (predominantly efavirenz), according to the presence of ≥1 TAM as the sole form of transmitted drug resistance. Results: Participants with ≥1 TAM comprised predominantly MSM (213 of 269, 79.2%), subjects of white ethnicity (206 of 269, 76.6%) and HIV-1 subtype B infections (234 of 269, 87.0%). Most (203 of 269, 75.5%) had singleton TAMs, commonly a revertant of T215Y or T215F (112 of 269, 41.6%). Over a median of 2.5 years of follow-up, 834 of 6599 (12.6%) subjects experienced viraemia (HIV-1 RNA >50 copies/mL). The adjusted HR for viraemia was 2.17 with PI/b versus NNRTI-based therapy (95% CI 1.88–2.51; P < 0.001). Other independent predictors of viraemia included injecting drug use, black ethnicity, higher viral load and lower CD4 cell count at baseline, and receiving abacavir instead of tenofovir. Resistance showed no overall impact (adjusted HR 0.77 with ≥1 TAM versus no resistance; 95% CI 0.54–1.10; P = 0.15). Conclusions: In this cohort, patients harbouring ≥1 TAM as the sole form of transmitted drug resistance gained no apparent virological advantage from starting first-line ART with a PI/b.